Management of antithrombotics in situations with a gap in evidence: A national French survey focusing on patients with coronary artery disease and atrial fibrillation. (1st February 2022) - Lemesle, Gilles; Bauters, Christophe; Bonello, Laurent; Fauchier, Laurent; Cayla, Guillaume; Marijon, Eloi; Guenoun, Maxime; Schurtz, Guillaume; Ninni, Sandro; Richardson, Marjorie; Albert, Franck; Cohen, Serge; et al.
Abstract: Background: If several randomized studies allowed to better apprehend what should be the best antithrombotic strategy in patients with concomitant coronary artery disease (CAD) and atrial fibrillation (AF), there are still several clinical situations with a gap of evidence. Methods: We conducted a national French survey in September–October 2020 among cardiologists in order to assess what are daily practices regarding the antithrombotic management in several specific clinical settings where no or little scientific evidence is available. The questionnaires were built by a committee of 6 cardiologists routinely involved in the field of CAD and/or AF. Results: Among the 6388 French cardiologists, 483 (7.6%) cardiologists participated to the survey. The rate of participation was rather homogeneous across the country. The mean age of participants was 48 +/− 12.7. There were 134 women (27.7%) and 349 men. Altogether, 181 (37.5%) cardiologists worked in private, 153 (31.7%) in non-universitary public and 83 (17.2%) in universitary public centers. The remaining had shared activity. Among the participants, 150 were interventional (coronary) cardiologists (31.1%). Others were general cardiologists ( n = 229), specialists in the field of rhythmology ( n = 43), heart failure ( n = 17) or imaging ( n = 44). The survey consisted of 10 questions pertaining to 2 virtual clinical scenarios. Conclusions: The present survey is an illustration of how therapeutic decisions may vary in such situations with little or no scientific evidence. Such surveys may help experts to build consensus (answers with little variability) and to target the need for future trials and more research (answers with a lot of variability). Highlights: Management of antithrombotics is critical in patients with concomitant coronary artery disease and atrial fibrillation There are several clinical situations with complete evidence gaps in this specific context Our survey is a perfect illustration of how therapeutic decisions may vary in situations with little scientific evidence Such surveys may help experts to build consensus and to target the need for future trials and more research.